Plum Cultivation in the Conditions of Navoi Region - Boboyorovich, Rajabov Doniyor; ugli, Isroilov Shavkat Shukhrat; Tursunovich, Mavlonov Bakhodir; Naimjonovich, Yarashev Komiljon (American Journal of Biology and Natural Sciences, 2025)
The article presents observational data aimed at determining the advantages of cultivating the plum variety “Yuzhnaya Krasavitsa” under the conditions of the Navoi region, as well as the impact of the region’s soil and climatic conditions on yield.